Evaluation of Laparoscopic‐Assisted Ovariohysterectomy for Treatment of Canine Pyometra. Issue 5 (10th April 2013) - Adamovich‐Rippe, Krista N.; Mayhew, Philipp D.; Runge, Jeffrey J.; Culp, William T. N.; Steffey, Michele A.; Mayhew, Kelli N.; Hunt, Geraldine B.
Abstract: Objective: To describe a technique for treating pyometra in dogs using a 3‐portal laparoscopic‐assisted ovariohysterectomy (LAOVH) and evaluate outcome. Study Design: Retrospective case series. Animals: Dogs (n = 12). Methods: Dogs with open or closed‐cervix pyometra with moderately sized (1–4 cm) uterine horn diameters based on preoperative ultrasonography and no evidence of perforation were included in the study. A 3‐portal technique for LAOVH was used. A wound retraction device was inserted into the caudal portal after enlargement of the incision to 3–4 cm to simplify removal of the uterus with minimal tension. Results: Twelve dogs (median weight, 23.3 kg; range, 2.1–46.0 kg) met the inclusion criteria. Median uterine diameter was 3.0 cm (range, 1.2–4.0 cm). Median surgical time for LAOVH was 107 minutes (range, 82–120 minutes). Complications included mild hemorrhage from the uterine vessels in 1 dog during uterine removal through the wound retraction device and intra‐abdominal uterine rupture in 1 dog which necessitated conversion to an open approach. All dogs recovered from surgery and were discharged. Conclusions: LAOVH can be used for treatment of select cases of canine pyometra. Careful case selection is mandatory to improve success and minimize conversion to an open approach. Gentle handling of the reproductive organs is imperative to avoid iatrogenic uterine rupture.